Salivary gland disease associated to human immunodeficiency virus - Daniele Manhães Caldas; Arley Silva Jr; Sandra R. Torres (Associação Brasileira de Odontologia, 2017)
The article by Lima et al.1 published in a recent edition provides relevant information about the prevalence of oral manifestations in children infected by human immunodeficiency virus (HIV).